Determinantes da capacidade absortiva: uma investigação empírica em pequenas e médias empresas inovadoras - Cassol, Alessandra (2018)
In today’s business world, the fact that very little is known about absorptive capacity (AC) in companies presents a real riddle towards the comprehension of the processes that compose it; in Brazil, for example, few studies have been able to approach this topic empirically and delve into its structuration. AC must be understood as a set of carefully analyzed routines in order to promote change and learning in companies. Therefore, this work is aimed at answering the following academical and empirical questions about AC: a) Which AC setups are commonly found in small and medium innovative businesses? b) Which among the processes that compose AC are more relevant to the development and consolidation of innovation? Therefore, this research aims at identifying, systematizing and analyzing the processes that compose the absorptive capacity in small and medium innovative businesses in Santa Catarina, in order to typify its main setups, its main consolidating processes and their relationship to innovation. The studied cases have revealed the relation between the capabilities, which evidences the recursiveness between the theoretical concepts, of Absorptive Capacity (AC) and Organizational Learning (OL). It is possible to observe that the generated knowledge can increase the companies capacity to absorb new knowledge, and once this process is completed, the level of knowledge is increased and OL is enhanced. Still, AC and OL change from company to company, for even though the source of knowledge, the intraorganizational environment and the networking are the same, the internal features affect the way in which new knowledge is received and used. The following work contributes to the presentation of settings, processes and practices which consolidate AC. These contributions are correlated, and support the yet unexplored recursiveness of the theme.